Norma Pernikahan Dalihan Natolu dan Padan pada Masyarakat Batak Toba dalam Film Mursala: Sebuah Kajian Sosiologi Sastra - Simatupang, Bintang Raphael Cornelius (Sabda: Jurnal Kajian Kebudayaan, 2024)
This research aims to reveal the marriage norms of Dalihan natolu and padan in the Toba Batak community in the film Mursala. The theories used in this research are film narrative theory according to Pratista and literary sociology according to Watt, namely literature as a mirror of society. The data collection method used is literature. Research is conducted through written and audio-visual sources such as videos. The material object of this research is the 100-minute film Mursala. The data taken are images and dialogue text in the film Mursala. The main formal object is marriage norms which are reviewed through the sociological theory of literature by Watt, namely literature as a reflection of society. Meanwhile, the presentation of the analysis results is in the form of a narrative description which is also accompanied by several pictures. The results of this research reveal that there are norms of natolu marriage and soul mate in the film Mursala, played by Anggiat Simbolon and Clarissa Saragih. The family relationship with the Anggiat clan, namely Simbolon and Clarissa, Saragih, are cousins based on the tarombo (genealogy) relationship as descendants of King Naiambaton. This makes their love relationship prohibited by the marriage norms of Dalihan Natolu and Padan. In the end, Anggiat Simbolon's love affair with Clarissa Saragih ended to avoid the heavy sanctions that apply to marriage norms in Toba Batak society, such as being expelled from her hometown and expelled from the scope of her clan. Apart from that, the customary sanctions that apply are related to myths and legends in the Toba Batak community and genetics in general. The Mursala film provides a moral message to the Toba Batak people, namely the importance of carrying out customs and norms that have been preserved for generations by the Ompu Sijolojolo Tubu (ancestors) so that they do not commit violations and are not subject to customary sanctions. More than that, this custom is carried out so that the Toba Batak people do not lose their identity as Toba Batak people. Keywords: Film Mursala, Batak Toba, dalihan natolu, padan, sosiologi sastra, naratif film.